Eziopatogenesi delle patologie del comportamento alimentare - Gebhardt, Eva (Il sogno della farfalla, 2013)
By firstly considering the characteristic psychological elements in patients affected by eating pathologies, such as the ideo-affective split or the problematic relationship with one’s body and bodily image, the article looks into the pathogenetic factors that arise in the early years of a child’s life in his relationship with the caregiver. During breastfeeding, the baby’s various affective experiences are memorized and if there is a coherence between signals and answers (physiological and affective), the child develops a coherent internal structure. In some mother-child couples, however, a poor contingency may occur between the affective behaviour of the child and the response of the mother, which may prove to be more intrusive, angry or distant. This may lead a child to experience difficulty in understanding his own emotional states. After many repeatedly disappointing experiences within a conflictual nursing experience it may happen that at the moment of weaning the child enacts an annulment drive, producing a loss of ego integrity. It is important to stress that in determining the direction of development in a physiological or pathological sense, what counts is the interaction between that child and that mother, that is the relationship that is established between the specific child and the specific expectations and qualities of the caregiver.